E-super vertex magic labeling of cartoon flowers and wounded flowers. Issue 3 (1st September 2020) - Nemani, Sarita; Joshi, Ganesh
Abstract: In this paper, we define a new class of graph called the cartoon flower and then show that E-super vertex magic labeling does not exist for the class of cartoon flower graphs. We further define the wounded cartoon flower graphs and establish some sufficient conditions for the graph not to be E-super vertex magic. We also give examples of some wounded cartoon flowers that admit an E-super vertex magic labeling and some others that do not.